Etanolmarknaden i Brasilien - Ohlsson, Patrik (2005)
According to the EC fuel regulations 2 % bio fuel has to be blended in all fuel by the year 2005, and 5.75 % by the year 2010, which means ethanol for gasoline driven vehicles, so there will be a substantial demand for ethanol. Brazil already has an established industry for producing ethanol and is the leading producer and exporter of fuel ethanol. My purpose with this paper is to investigate why Brazil decided to develop ethanol production on a large-scale operation and to find out today's situation. Focus will mainly be on ethanol production with sugarcane as a feedstock. To gather information the databases Agricola and Agris was used, and also the search program google.se on the Internet. The two oil crises in the seventies had a big impact on the Brazilian economy. Brazil's balance of payment deficits was negative at that time. 1980 Brazil used 48.7 % of the income from exports to pay for the import of crude oil. To the politicians it was clearly that something had to be done. Brazil has a long tradition of producing ethanol from molasses from the sugar extraction of sugarcane. The sugarcane industry, with its high capacity and decreasing profitability was an important reason for the implement of the Proalcool program that was launched in 1975. It was three important means for the Proalcool program, namely: to reduce the country's dependence on oil imports, to balance the payment deficits, and the decreasing international raw sugar prices. Brazil has very good conditions for growing sugarcane; sugarcane can be cultivated almost year round, and sugarcane is cultivated in very big units; 10 000 hectares to 45 000 hectares/unit. The sugarcane cultivation requires a lot of labour and almost two-thirds of the cost of producing ethanol is labour costs. The ethanol is produced in either an annexed distillery or an autonomous. In the annexed distillery molasses is used to produce ethanol and in the autonomous plant ethanol is obtained from sugarcane. Normally 96 % of the sugar can be extracted from the cane, and bagasse, the residue contains 50 % water. The Bagasse stands for more than half of the heating value in sugarcane and in a typical Brazilian facility all the bagasse is burned for the electricity and steam needed for the process. Some plants are even capable of selling surplus electricity to the grid. There are two kinds of ethanol produced: anhydrous, which contains no water and hydrous, or hydrated which contains some five percent of water. The anhydrous ethanol, with 99.5 % alcohol can be used as a blend in gasoline, up to 16-17 % without alternations in engines. The hydrated ethanol, with 95 % alcohol is used as a neat fuel in E100 cars. Ethanol contains 60 % of the energy value of gasoline but gives higher torque and peak performance, so an E100 car will use about 15- 20 % more fuel/mile.